Government Expenditure Arrears : Securitization and Other Solutions - Ramos, Alberto (IMF Working Papers; Working Paper ;, 1998)
On occasions, by running arrears, governments have unilaterally borrowed from domestic agents. These agents ended up with implicit claims on the government for which they had no title and that would be honored, at best, on an unspecified future date and for an uncertain value. Having untitled assets limits creditors' financial management capacity, because they cannot trade or enforce these claims. This paper presents several options for addressing the arrears problem. It recommends that the government recognize its implicit financial liabilities, set a timetable for their clearance, and issue market-negotiable titles (securitize). Several country experiences with securitization operations are documented.